Effectiveness of Ifdil perceptual light therapy in reducing post-traumatic stress disorder of Lombok’s earthquake victims - Ifdil, Ifdil; Fadli, Rima Pratiwi; Amalianita, Berru; Zola, Nilma; Putri, Yola Eka; Suhartiwi, Suhartiwi; Taufik, Taufik (Universitas Negeri Padang, 2022)
Earthquake as a disaster experienced by various regions, especially Lombok, caused psychological disturbances for its victims. These psychological disorders include post-traumatic stress disorder (PTSD) which arise when the same symptoms occur when an earthquake is experienced. The victim experienced a severe psychological condition due to sensory and perception of the earthquake as a dangerous thing. The victims of this earthquake need to get psychological treatment. The research objective is to examine teh effectiveness of Ifdil Perceptual Light Technique for Reducing Post-Traumatic Stress Disorder (PTSD). Ifdil perceptual light technique (IPLT) is one of the treatments that can be given to overcome PTSD caused of earthquake. Intervention using IPLT through sensory and perceptual modification of individuals through the light spectrum.This research uses single-subject design to seven subjectwho have experience a PTSD symptom of earthquake.Design research using design A-B-A single subject research. The instrument used are observation, interview, scaling technique and DSM-IV.Data were analyzed using the nonparametricWilcoxon signed-rank test. The result indicate that the respondents were high PTSD level before given IPLT. However after treatment, the symptom levels of respondents decreased. On the basis of the Wilcoxon test results, it also was found that the PTSD level of respondent before and after the IPLT’S treatment declined. The result shows that IPLT is effective in reducing PTSD disorders in earthquake victims. IPLT can be one alternative treatment in helping earthquake victims who experience psychological disorders.